2020
DOI: 10.1021/acsomega.0c01949
|View full text |Cite
|
Sign up to set email alerts
|

White-Light Emission and Tunable Luminescence Colors of Polyimide Copolymers Based on FRET and Room-Temperature Phosphorescence

Abstract: Thermally stable copolyimide (CoPI) films exhibiting high optical transparency and room-temperature phosphorescence (RTP) were prepared by copolymerizing fluorescent dianhydride and brominated phosphorescent dianhydride with an alicyclic diamine. The CoPI films underwent a 5 wt % degradation at a temperature higher than 349 °C and exhibited dual fluorescent and phosphorescent emissions owing to their efficient Förster resonance energy transfer from the fluorescent to phosphorescent dianhydride moieties in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…However, white light generated by combining plural fluorophores often faces problems such as re-absorption, phase separation, and temporal change in emission colors. Meanwhile, white light can also be obtained from a single phase or a single molecule, by introducing two or three light-emitting elements into a single molecule [4] and single polymer [5], or using organic-inorganic hybrid semiconductors [6], metal complexes [7], and room-temperature phosphorescent polymers [8]. Achieving white light from a single-phase or molecule is beneficial because of their stability of luminescent color, ability to avoid phase separation, and simple manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, white light generated by combining plural fluorophores often faces problems such as re-absorption, phase separation, and temporal change in emission colors. Meanwhile, white light can also be obtained from a single phase or a single molecule, by introducing two or three light-emitting elements into a single molecule [4] and single polymer [5], or using organic-inorganic hybrid semiconductors [6], metal complexes [7], and room-temperature phosphorescent polymers [8]. Achieving white light from a single-phase or molecule is beneficial because of their stability of luminescent color, ability to avoid phase separation, and simple manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Förster resonance energy transfer (FRET) is a well-known energy transfer phenomenon [35], in which the excitation energy between two chromophores in close distance is directly transferred through non-radiative dipole-dipole coupling, and has been applied to white light-emitting materials [36]. We have also reported a white-light fluorescent PI copolymer based on FRET and room-temperature phosphorescence [8]. ESIPT is a process in which the excited state is relaxed by the structural relaxation (tautomerization) from the normal (N*) form to the tautomer (T*) form, through proton transfer in the excited state, resulting in a large energy gap between the absorption and emission, leading to a very large ν.…”
Section: Introductionmentioning
confidence: 99%
“…The present authors recently reported a novel white-light emitting PI film by copolymerizing a fluorescent and a phosphorescent PIs [5,12]. Moreover, we have also reported that, by introducing heavy halogens, iodine and bromine, into the dianhydride moiety of PIs, bright phosphorescence (Ph) can be observed at room temperature owing to the heavy atom effect [13,14].…”
Section: Introductionmentioning
confidence: 81%
“…19 However, many multicomponent PL systems possess intra-or intermolecular energy transfer (ET) mechanisms such as Fluorescence Resonance Energy Transfer (FRET). 11,13,14,20,21 Accounting for ET processes makes applying colour-mixing theory a challenge since ET differs from system to system. However, what if ET processes were mitigated or suppressed?…”
Section: Introductionmentioning
confidence: 99%